Mobile Service Robotics 2014
DOI: 10.1142/9789814623353_0044
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Swing-Leg Retraction in Human Locomotion

Abstract: Swing-leg retraction, the backward rotation of the swing leg just prior to ground contact, is observed in human locomotion. While several advantages of swingleg retraction, like gait stability and perturbation rejection, are shown by conceptual models, there is currently very little experimental data on swing-leg retraction in human motion. In this paper, kinematic data for twenty-eight subjects walking and running at different speeds are analyzed. Swing-leg retraction was shown to exist in walking and running… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…However, additional detection rule sets may improve the signal quality and render the thigh a reliable source to differentiate gait phases. When using the additional rule sets for the shank, the leg, and the extended leg, we found a systematic bias of early detection for the heel-strike event (with IMU and Motion capture), which was found to be a typical human gait characteristic in previous work (swing leg retraction; Seyfarth et al, 2003; Poggensee et al, 2014). In comparison, early, on-time and late detection were identified for toe-off.…”
Section: Discussionmentioning
confidence: 51%
“…However, additional detection rule sets may improve the signal quality and render the thigh a reliable source to differentiate gait phases. When using the additional rule sets for the shank, the leg, and the extended leg, we found a systematic bias of early detection for the heel-strike event (with IMU and Motion capture), which was found to be a typical human gait characteristic in previous work (swing leg retraction; Seyfarth et al, 2003; Poggensee et al, 2014). In comparison, early, on-time and late detection were identified for toe-off.…”
Section: Discussionmentioning
confidence: 51%
“…In general, the efficiencies of an actuator for doing positive and negative work can be different (1) . For example, human muscles have about 25% and 120% efficiency for positive and negative (2) work, respectively. 12,28 If the positive quantities 1/c 1 and 1/c 2 are the efficiencies of positive and negative work, respectively, or equivalently c 1 and c 2 are the cost of unit positive and unit negative work, then the net energetic cost of doing W + positive work and W − negative work (W − < 0) is…”
Section: Energetic Cost Of Impulsive Push-off Force and Retraction Tomentioning
confidence: 99%
“…In a normal walking or running step of humans and animals, the non-contact leg swings forward then is rapidly decelerated and, in most cases, begins to move rearward shortly before the swing foot contacts the ground. 1,2 This rearward rotation of the swing leg prior to touch-down, known as swing-leg retraction, is visible in most slow motion videos of running. 3 It is more difficult to see in walking due to the short duration of the retraction phase and small angular velocities of the leg at the end of swing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human leg retracts at the end of the swing phase just before the leg collides with ground (i.e., heel-strike) [1]. It was shown that hip retraction exists in human motion for a wide range of walking and running speeds [2]. Leg retraction was also observed in animal locomotion [3].…”
Section: Introductionmentioning
confidence: 99%